Surface Architecture of Histoplasma Capsulatum - Guimaraes, Allan J.; de Cerqueira, Mariana D.; Nosanchuk, Joshua D. (Frontiers in Microbiology, 2011)
The dimorphic fungal pathogen Histoplasma capsulatum is the most frequent cause of clinically significant fungal pneumonia in humans. H. capsulatum virulence is achieved, in part, through diverse and dynamic alterations to the fungal cell surface. Surface components associated with H. capsulatum pathogenicity include carbohydrates, lipids, proteins, and melanins. Here, we describe the various structures comprising the cell surface of H. capsulatum that have been associated with virulence and discuss their involvement in the pathobiology of disease.